The limits of neoliberalism authority, sovereignty and the logic of competition - Davies, William 1976- (Theory, culture & society, 2017)
This text examines the efforts and failures of economic experts to make government and public life amenable to measurement, and to re-model society and state in terms of competition. It explores the practical use of economic techniques and conventions by policy-makers, politicians, regulators and judges and how these practices are being adapted to the perceived failings of the neoliberal model. Revised edition includes a new preface from the author and a foreword by Aditya Chakrabortty.